Respuesta :
The k-th root's inverse function is raising to the k-th power.
So, if we raise the k-th root of some number x to the k-th power, we have applied a function and its inverse to x, and we must get x itself as output:
[tex]f(f^{-1}(x))=f^{-1}(f(x))=x\quad\text{for every invertible function f}[/tex]
So, in our case, we have
[tex](\sqrt[k]{x})^k = \left(x^{\frac{1}{k}}\right)^k=x^{k\cdot \frac{1}{k}}=x^1=x[/tex]
The equation that Arlene claim should be [tex]x^{k.\frac{1}{k}} \ = x^1 = x[/tex]
Equation:
The k-th root's inverse function should be raising with respect to the k-th power.
Thus, in the case if we raise the k-th root of some number x to the k-th power, so here we used the function and its inverse to x, and we must get x itself in an output:
So,
[tex](k \sqrt x)^k = (x\frac{1}{k})^k = x^{k.\frac{1}{k}} \ = x^1 = x[/tex]
learn more about the expression here: https://brainly.com/question/24686935